Some taxation options granted to the non- resident taxpayer under the IRS: analysis of the legislator’s motivation and the legal-fiscal consequences - Martins, Sandra (Revista Jurídica Portucalense, 2021)
The Personal Income Tax Code contains numerous legitimate taxation options, which are available to the taxable person, due to the inherent legal and fiscal freedom, and which allow them to achieve the much-desired tax savings. In this sense, we intend to list and develop some of the options granted to the taxable person residing in another Member State of the European Union or the European Economic Area, following an approach that focuses not only on clarifying the option itself and the type of taxable person, as in the motivation outlined by the tax legislator in the introduction of these alternatives and the underlying advantages and disadvantages.